Clinical curative effect of neoadjuvant chemotherapy combined with immunotherapy and its impact on immunological function and the expression of ER, PR, HER-2 & SATB1 in HER-2-Positive breast cancer patients - Chen, Zhi; Sang, Mei-xiang; Geng, Cui-zhi; Hao, Wei; Jia, Hui-qun (Pakistan journal of medical sciences, 2022)
Objective: To evaluate the clinical curative effect of neoadjuvant chemotherapy combined with immunotherapy and its impact on immunological function and the expression of ER, PR, HER-2 and SATB1 in HER-2-positive breast cancer patients. Methods: The subjects of study were 80 patients with HER-2-positive breast cancer. Enrolled patients were randomly divided into two groups, with 40 cases in each group at The Fourth Affiliated Hospital of Hebei Medical University from March 2018 from March 2021. Patients in the control group were provided with neoadjuvant chemotherapy using TAC regimen merely; while those in the study group received oral administration of Apatinib Mesylate (500mg/d; three weeks a cycle) on the basis of the TAC regimen. Further comparative analysis was performed focusing on the therapeutic effect and adverse drug reaction rate of the two groups; levels of CD3+, CD4+, CD8+ and CD4+/CD8+ of T lymphocyte subsets in the two groups before and after treatment; as well as the expressions of ER, PR, HER-2 and SATB1 in the two groups before and after treatment. Results: The total response rate was 77.5% and 55% in the study group and the control group, respectively, with an obviously better outcome in the former group than that in the latter group (p=0.03). Meanwhile, the incidence of adverse reactions was 40% in the study group and 45% in the control group, without statistical difference (p=0.65). There were statistically significant differences that the levels of CD3+, CD4+, and CD4+/CD8+ in the study group were significantly higher when compared with those in the control group after treatment (CD3+, p=0.00; CD4+, p=0.02; CD4+/CD8+, p=0.00); while no evident change was observed in the level of CD8+ (p=0.88). After treatment, the positive expression rates of ER, HER-2 and SATB1 were remarkably lower in the study group than those in the control group, showing statistically significant differences (ER, HER-2, p=0.03; SATB1, p=0.02). However, there was no statistically significant difference in the positive expression rate of PR between the study group and the control group (P=0.80). Conclusions: Neoadjuvant chemotherapy combined with immunotherapy has significant effect on the treatment of HER-2-positive breast cancer patients. It can result in the significant enhancement of T lymphocyte function, obvious improvement in the negative converse rates of ER, HER-2 and SATB1, and no evident increase in the adverse drug reactions. The proposed therapeutic approach is safe, effective, and have certain clinical value. doi: https://doi.org/10.12669/pjms.38.3.5199 How to cite this:Chen Z, Sang M, Geng C, Hao W, Jia H. Clinical curative effect of neoadjuvant chemotherapy combined with immunotherapy and its impact on immunological function and the expression of ER, PR, HER-2 and SATB1 in HER-2-Positive breast cancer patients. Pak J Med Sci. 2022;38(3):---. doi: https://doi.org/10.12669/pjms.38.3.5199 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.